Synthesis, Physico-chemical and Antimicrobial Studies of Diketones, Disemicarbazones and Pentaaza Dispiro Tetradecaenes - Thilakam, R.; Jayamani, V.; Kalpana, R.; Gayathiri, A.K. (Asian Journal of Chemistry, 2010)
A new class of piperidin-4,5-diones (1a-3a), disemicarbazones (1b-3b) and pentaaza dispiro tetradecadienes (1c-2c) have been synthesized and characterized by analytical and spectral data. All the compounds were also evaluated for their antimicrobial activity.